A cross-sectional survey of knowledge, attitude, and practices toward dengue fever among university students in Bengaluru - B. S., Shylaja; John, Denny (International Journal of Contemporary Pediatrics, 2025)
Background: The incidence of dengue fever (DF) has been on the rise over the past few decades, with an increasing number of outbreaks in Bengaluru. This study was conducted to assess health literacy on DF among university students through a knowledge, attitude, and practices (KAP) survey. Methods: A cross-sectional survey among university students between the ages of 18 and 21 was carried out. Data was collected using a validated questionnaire comprising 40 questions based on KAP on dengue, to assess the KAP regarding DF, descriptive statistic; univariate and multivariate logistic regressions were performed. Results: Among 340 students, 104 (30.6%) showed a good level of knowledge, 154 (45.3%) exhibited a good attitude level, 255 (75%) displayed good preventive practice levels, and 173 (50.9%) demonstrated good overall KAP levels. 24.4% (n=83) reported of prior dengue infection history in family. Private university attendance correlated with lower odds of positive attitudes (OR=0.562, p=0.012) and overall KAP levels (OR=0.618, p=0.032) in univariate analysis, a trend confirmed in multivariate analysis (aOR=0.393, p=0.001 for attitude; aOR=0.570, p=0.035 for KAP levels). Conclusions: The study revealed strong awareness, positive attitudes, and preventive behaviours among Bengaluru university students regarding DF. Location and institution type influenced attitudes, emphasizing the need for targeted health literacy programs for effective dengue prevention in urban areas such as Bengaluru.